2004
DOI: 10.1590/s1415-43662004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Índices morfofisiológicos e de produção de alface sob estresse salino

Abstract: No Nordeste brasileiro, a alface é uma importante olerícola cultivada sob condições de irrigação em que são utilizadas águas de qualidade variada; uma das características da região é a variação espacial e temporal da qualidade dos recursos hídricos. Mesmo assim, são escassos os trabalhos referentes aos efeitos da salinidade na formação de mudas e seu reflexo sobre a produção. Neste trabalho estudaram-se os efeitos de cinco níveis de condutividade elétrica da água de irrigação (CEa: 0,3, 1,0, 1,7, 2,4 e 3,1 dS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
20

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
2
4
0
20
Order By: Relevance
“…For the period of 15-21 DAT, AGR-SFM values decreased and adjusted to the linear model, with a reduction of 17.5% per unit increase of ECw, i.e., the high levels of ECw caused a sharp reduction of the AGR-SFM in this period, which reached 91% (1.8 g d -1 ) for the treatment using 5.2 dS m -1 water, compared with the control (19.7 g d -1 ). The results for AGR-SFM observed in this study corroborate those obtained by Viana et al (2004), who also observed a reduction of AGR-SFM with the increase in the water salinity level for all evaluation periods (0-10, 10-20 and 20-30 DAT), when evaluating the effect of five water EC levels (0.3, 1.0, 1.7, 2.4 and 3.1 dS m -1 ) on the morphophysiological production parameters of lettuce.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For the period of 15-21 DAT, AGR-SFM values decreased and adjusted to the linear model, with a reduction of 17.5% per unit increase of ECw, i.e., the high levels of ECw caused a sharp reduction of the AGR-SFM in this period, which reached 91% (1.8 g d -1 ) for the treatment using 5.2 dS m -1 water, compared with the control (19.7 g d -1 ). The results for AGR-SFM observed in this study corroborate those obtained by Viana et al (2004), who also observed a reduction of AGR-SFM with the increase in the water salinity level for all evaluation periods (0-10, 10-20 and 20-30 DAT), when evaluating the effect of five water EC levels (0.3, 1.0, 1.7, 2.4 and 3.1 dS m -1 ) on the morphophysiological production parameters of lettuce.…”
Section: Resultssupporting
confidence: 91%
“…The results for RGR-SFM obtained in this study confirm those found by Viana et al (2004), studying lettuce, and by Santos et al (2013), who found influence of water salinity on the relative growth rate of castor bean plants.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Das equações lineares apresentadas na Figura 4, calculase um decréscimo no consumo hídrico de 9,22% para cada g L -1 de NaCl, no Experimento I. Para o Experimento II, por sua vez, a redução foi de 3,69% para cada g L -1 de NaCl; este resultado demonstra que o uso combinado de águas doce e solobras adotado no Experimento II pode representar menor restrição à absorção de água pelas plantas, o que se constitui uma vantagem comparativa ao Experimento I, já que diversas pesquisas têm reportado o efeito da salinidade sobre a diminuição da transpiração e, por conseguinte, da produtividade das culturas (Viana et al, 2004;Cavalcanti et al, 2005;Correia et al, 2005;Ruiz-Sánchez et al, 2000). A diminuição da área foliar representa uma demanda menor de água e é considerada um mecanismo de adaptação das plantas às condições salinas, uma vez que quanto maior a salinidade do meio maior também é a dificuldade para absorção de água; esta é uma assertiva fisiológica para todo tipo de cultivo, inclusive o hidropônico, no qual a abundância de água não impede a dificuldade em sua absorção na condição salina.…”
Section: Resultsunclassified
“…A salinidade, tanto dos solos como das águas, é uma das principais causas da queda de rendimento das culturas (Flowers, 2004), devido aos efeitos de natureza osmótica, tóxica ou nutricional (Viana et al, 2004). Entretanto, os efeitos dependem, ainda, de outros fatores, como espécie, cultivar, estádio fenológico, tipos de sais, intensidade e duração do estresse salino, manejo cultural e da irrigação e condições edafoclimáticas (Tester e Davénport, 2003).…”
Section: Introductionunclassified